Features of the organization of accounting and control of own capital of banks of the second level - Kassymbekova, G.R. (Journal of Economic Research & Business Administration, 2016)
In this article value and a role of accounting and control of own capital of banks of the second level as bases of all registration and analytical information on a financial condition of bank are in detail considered.The author shows features of the accounting of authorized capital, the reserve capital, retained earnings of banks of the second level of the Republic of Kazakhstan.In article one of the main forms of the reporting of own capital of bank used in banking practice by drawing up the reporting according to Interna tional Financial Reporting Standards is also studied.At the same time, in article Basel of III in a section countries, including RK is given experience of introduction of standards. Prospects and possible negative consequences of transition to new requirements of sufficiency of own capital of banks of the second level are given.